Use of oxytetracycline in the treatment of canine ehrlichiosis: a retrospective study of 15 cases in Camagüey, Cuba - Peña G., Iván (2018)
A retrospective study of 15 canine patients from the neighborhoods of Camagüey, Cuba in the period 2016-2017, with clinical signs compatible with hemoparasitosis and laboratory diagnosis by blood smear and Giemsa coloration of canine ehrlichiosis. An alternative therapy with antianemic reconstitutes, hydration with Lactate Ringer and oxytetracycline was proposed for the treatment of canine ehrlichiosis.